2009
DOI: 10.1002/jcp.21922
|View full text |Cite
|
Sign up to set email alerts
|

Activation of nuclear factor kappa B in mammary epithelium promotes milk loss during mammary development and infection

Abstract: We investigated whether Nuclear Factor-kappa B (NF-κB), which exhibits a regulated pattern of activity during murine mammary gland development, plays an important role during lactation and involution, when milk production ceases and the gland undergoes apoptosis and remodeling. We generated a doxycycline inducible transgenic mouse model to activate NF-κB specifically in the mammary epithelium through expression of a constitutively active form of IKK2, the upstream kinase in the classical NF-κB signaling cascad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
61
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 37 publications
2
61
0
Order By: Relevance
“…Among many findings, these studies illustrate that the inflammatory response is modulated by interactions with CD14, and that it results in a neutrophil influx regulated by mammary alveolar macrophages. As suggested in both our previously published work 4 , as well as that of others 2 this model of mastitis may be further used to study mechanisms and therapeutics relevant in humans, where as many as 3-33% of breastfeeding women suffer from this painful infection (percentage varies based on study methodology) 15 . It may also prove a useful research tool for those in the dairy industry, where mastitis is a costly disease leading to significant losses in milk production each year 16 .…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Among many findings, these studies illustrate that the inflammatory response is modulated by interactions with CD14, and that it results in a neutrophil influx regulated by mammary alveolar macrophages. As suggested in both our previously published work 4 , as well as that of others 2 this model of mastitis may be further used to study mechanisms and therapeutics relevant in humans, where as many as 3-33% of breastfeeding women suffer from this painful infection (percentage varies based on study methodology) 15 . It may also prove a useful research tool for those in the dairy industry, where mastitis is a costly disease leading to significant losses in milk production each year 16 .…”
Section: Discussionmentioning
confidence: 86%
“…This method was successful and allowed us to study the inflammation associated with LPS injection without any additional effects overlaid by the process of injection. In addition, this method also utilized an NF-κB luciferase reporter transgenic mouse and bioluminescent imaging technology to visually and quantitatively show increased NF-κB signaling within the LPS-injected gland 4 .These methods are of interest to researchers of many disciplines who wish to model disease within the lactating mammary gland, as ultimately, the technique described here could be utilized for injection of a number of substances, and is not limited to only LPS. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of NF-B signaling has been shown to result in a decrease in caspase-3 cleavage and delayed involution (11). In contrast, a previous study demonstrated that constitutively active IKK-␤ increased NF-B activation, leading to a reduction in milk protein levels and increases the level of apoptosis during involution (10).…”
mentioning
confidence: 94%
“…However, the activation of STAT3 is insufficient to induce involution in the absence of NF-B signaling. During mammary gland development, the activation of NF-B increases during pregnancy, decreases during lactation, and then increases again after weaning (9,10). The loss of NF-B signaling has been shown to result in a decrease in caspase-3 cleavage and delayed involution (11).…”
mentioning
confidence: 99%